Analisis Penerapan Forecasting Penjualan Untuk Menentukan Jumlah Tenaga Kerja Efektif Produksi Tepung Mocaf Pada UMKM XYZ - Wahyu Hadi Sutiyono; Widya Setiafindari (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Sales forecasting is a technique that companies use to predict future sales volumes based on previous sales data. This research aims to help UMKM XYZ determine the optimal production amount to maximize profits, by using forecasting methods in planning mocaf flour production. The methods used include the Time Series model with Moving Average, Exponential Smoothing, and Trend Analysis, which are calculated using POM QM Windows software. The analysis results show that the Trend Analysis method is the most accurate for forecasting, with the smallest error value, namely MAD of 76.997, MSE of 8161.672, and MAPE of 6.02%. The smaller the error value, the more accurate the forecasting results. Therefore, the Trend Analysis method is recommended for forecasting mocaf flour sales in XYZ UMKM in 2024, with the production of 15,100 kg to avoid excess stock and dead stock in meeting consumer demand.